Answer:
f(x) + g(x) = x² - 10x + 9
General Formulas and Concepts:
<u>Algebra I</u>
Step-by-step explanation:
<u>Step 1: Define</u>
f(x) = x² - 11x + 18
g(x) = x - 9
<u>Step 2: Find f(x) + g(x)</u>
- Substitute: f(x) + g(x) = x² - 11x + 18 + x - 9
- Combine like terms (x): f(x) + g(x) = x² - 10x + 9
<u />
<span>associative property of multiplication
answer
</span><span>4 ∙ (3 ∙ 6) = (4 ∙ 3) ∙ 6 </span>
Answer:
7x^6×(9×^6-5)
Step-by-step explanation:
63x^12-35x^6
7x^6×(9×^6-5)
So in order to solve you must first combine like terms.
-2y + 2y + 3 = 3
0 + 3 = 3
Subtract 3.
0 = 0
The answer is infinate solution because both numbers are the same.
I hope this helps love! :)